(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The article highlights the results of experiments on researching the bioecological development of dominant pest species in pastures of ephemeral-ephemeroid vegetation in the southern and central regions of the Republic of Uzbekistan.